Information technology in library management (Anmol Pubications, 2001)
Contents of material: 1/ Introduction. 2/ Computer in library management. 3/ Software installation. 4/ Online computer service. 5/ Electronic service delivery. 6/ Terminal software. 7/ Computer selection. 8/ Library network hardware. 9/ Multimedia catalog. 10/ Library networking.